2023
DOI: 10.1111/irv.13135
|View full text |Cite
|
Sign up to set email alerts
|

Genomic surveillance of SARS‐CoV‐2 strains circulating in Iran during six waves of the pandemic

Abstract: Background SARS‐CoV‐2 genomic surveillance is necessary for the detection, monitoring, and evaluation of virus variants, which can have increased transmissibility, disease severity, or other adverse effects. We sequenced 330 SARS‐CoV‐2 genomes during the sixth wave of the COVID pandemic in Iran and compared them with five previous waves, for identifying SARS‐CoV‐2 variants, the genomic behavior of the virus, and understanding its characteristics. Methods After viral RNA extraction from clinical samples collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
2
3
0
Order By: Relevance
“…The measured higher RT-qPCR positivity among children in the low socioeconomic group in our study could be explained based on the limited access to hand sanitizers and personal protective equipment, such as masks, living in a more densely populated area, and the different housing conditions, making isolation of the infected household members difficult [ 36 , 37 ]. In the present study, a higher prevalence of SARS-CoV-2 infection was detected according to the PCR results in spring of 2021, which is consistent with the early course of a new wave of COVID-19 (April to June 2021) caused by more contagious variants (i.e., alpha and delta variants) in Iran [ 38 , 39 ]. Our findings showed that SARS-CoV-2 infection was significantly lower in children with smoking parents compared with the nonsmoking ones.…”
Section: Discussionsupporting
confidence: 86%
“…The measured higher RT-qPCR positivity among children in the low socioeconomic group in our study could be explained based on the limited access to hand sanitizers and personal protective equipment, such as masks, living in a more densely populated area, and the different housing conditions, making isolation of the infected household members difficult [ 36 , 37 ]. In the present study, a higher prevalence of SARS-CoV-2 infection was detected according to the PCR results in spring of 2021, which is consistent with the early course of a new wave of COVID-19 (April to June 2021) caused by more contagious variants (i.e., alpha and delta variants) in Iran [ 38 , 39 ]. Our findings showed that SARS-CoV-2 infection was significantly lower in children with smoking parents compared with the nonsmoking ones.…”
Section: Discussionsupporting
confidence: 86%
“…The results showed the circulation of alpha variant until July 2021 and afterward delta variant was detected when Iran was in the fourth wave of the COVID‐19 pandemic. Consistent with what we reported, Yavarian et al and Sadeghi et al reported the circulation of alpha (GRY clade) and delta variants (GK clade) during the fourth wave of COVID‐19 in Iran 12,13 …”
Section: Discussionsupporting
confidence: 92%
“…Among alpha variants Pts of COVID-19 in Iran. 12,13 In this study, monitoring and comparing intrahost evolution showed considerable variations in immunocompromised patients after treatment. In Pt 4 on Day 79 after RDV treatment S-L452M was observed.…”
Section: Sars-cov-2 Genome Analysismentioning
confidence: 80%
“…We categorized patients into the last three waves based on reports that recognized distinct waves in different months in Iran. 8 , 14 The fourth wave in Iran was defined as the period from April 9 to June 10, 2021, the fifth wave was defined as the period between August 9 and October 10, 2021, and the sixth wave was defined as the period between January 20 and May 22, 2022. Variant‐specific PCR was used for the validation of SARS‐CoV‐2 variants in the community.…”
Section: Methodsmentioning
confidence: 99%